2016
DOI: 10.4236/gsc.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of Guar Gum Grafted Acrylic Acid/Nanoclay Superabsorbent Composites and Its Use in Crystal Violet Dye Absorption

Abstract: Natural gums can be tailored and used for the removal of toxic dyes like crystal violet via grafting techniques. However, grafting via microwave irradiation showed both higher yield and fast reaction kinetics as compared to conventional grafting. Silane modified nanoclay has been used to prepare acrylic acid grafted guar gum nanocomposites via microwave irradiation technique. The grafting was confirmed via infra-red spectroscopy while XRD diffractograms suggested exfoliation of modified nanoclay in guar gum gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 36 publications
3
11
1
Order By: Relevance
“…This is mainly attributed to the in-situ grafting of guar gum with acrylic acid along with nanoclay and sonication. A similar observation was made in our earlier work [15] and Yoonessi et.al., [18]. A similar trend is observed for guargum/MWCNT composites wherein, the peaks of MWCNT disappear.…”
Section: Adsorption Isotherm Modelssupporting
confidence: 92%
See 2 more Smart Citations
“…This is mainly attributed to the in-situ grafting of guar gum with acrylic acid along with nanoclay and sonication. A similar observation was made in our earlier work [15] and Yoonessi et.al., [18]. A similar trend is observed for guargum/MWCNT composites wherein, the peaks of MWCNT disappear.…”
Section: Adsorption Isotherm Modelssupporting
confidence: 92%
“…Hence it has a promising potential for removal of both heavy metals and dyes from waste water [14]. Our earlier work on guar gum grafted acrylic acid with nanoclay gave encouraging results [15] for removal of crystal violet dye. In that study the emphasis was mainly on microwave assisted synthesis and optimization…”
Section: Removal Of Crystal Violet Dye Using Grafted Guar Gum Along W...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been reported on guar gum-based composites for the removal of organic dyes from aqueous solutions. For instance, Shruthi et al studied the efficiency of the guar gum-grafted acrylic acid/nanoclay composite on the adsorption of crystal violet dye and reported that it requires at least three hours to reach the maximum dye adsorption capacity of 12.5 mg/g [65]. Saxena and Sharma investigated the adsorption and kinetic studies on the removal of methyl red dye from aqueous solution using guar gum powder, which showed a monolayer dye adsorption capacity of 66.66 mg/g in three hours at pH 4.2 [66].…”
Section: Decolorization Of Mbmentioning
confidence: 99%
“…It has been found that synthetic polymer-based gel has potential to work at in low or high reservoir temperature. Guar gum grafted acrylonitrile (GG-g-PAN) has been synthesized by the various combination of polymerizations, for example okra grafted acrylonitrile (Mishra and Pal, 2007), chitosan grafted acrylonitrile (Singh et al, 2004), guar gum grafted acrylic acid (Shruthi et al, 2016) and guar gum grafted acrylonitrile (Thimma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%